Efforts To Improve Student’s Learning Outcomes In Science Learning Through Contextual Strategy In MI (Elementary School) Academic Year 2018/2019 - Prayoga, Muhammad Fery; Anas, Nirwana; Usiono, Usiono; Marwa, Atikah (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Contextual learning was learning that allowed students to strengthen, expand, and apply their academic knowledge and skills in a variety of settings in school and outside of school to solve real-world problems or simulated problems. This study aimed to: 1) viewed student learning outcomes before contextual learning strategies were applied; 2) saw student learning outcomes after applying contextual learning strategies; 3) improved student learning outcomes through the implementation of contextual learning strategies. This research was conducted at one of the Private Madrasah Ibtidaiyah (MIS) in North Sumatra. The subjects in this study were 28 students in Class IV. The research design was Classroom Action Research (CAR) developed by Arikunto. The results showed: 1) The average results of students before applying contextual learning strategies was 10.8%; 2) average learning outcomes after contextual learning strategies were applied is 86.80%; 3) an increase in learning outcomes through the implementation of contextual learning strategies. This study recommends that other researchers research contextual learning strategies in other subjects